Amplification of FISH signals using intermittent microwave irradiation for analysis of chromosomal instability in gastric cancer. Issue 6 (1st December 1999) - Kitayama, Y; Igarashi, H; Sugimura, H
Abstract : Gastrointestinal tract tumours are notorious for their difficulty in relation to conventional cytogenetic analysis. In particular, necrosis, the presence of stromal inflammatory and other cells, and poor attachment of tumour cells have led to problems with the quality and reliability of cytogenetic preparations, even with the recently developed fluorescence in situ hybridisation (FISH) technique. Furthermore, background autofluorescence masks the weak hybridisation signals in the nuclei. To overcome this problem, brief microwave treatment was applied for the identification of centromeres by in situ hybridisation in gastric cancer cells. Using this technique, a panel of 17 centromeric specific alpha-satellite probes was used to detect chromosomal instability in these cells. Lymphocyte controls and cancer cells subjected to irradiation achieved the hybridisation threshold in 30 minutes, providing a significant difference when compared with the non-irradiated samples (mean (SD) frequency of diploid cells 97% (2.1%) v 76% (4.6%), respectively). Therefore, this protocol of intermittent microwave treatment is recommended as a simple, rapid, and highly reproducible technique for application to various types of probe. It also gives well defined hybridisation signals and reduces background "noise".